The Microbiome–Gut–Brain Axis, a Potential Therapeutic Target for Substance-Related Disorders - Fu, Xuan; Chen, Ti; Cai, Jingda; Liu, Bo; Zeng, Yaohui; Zhang, Xiaojie (Frontiers in Microbiology, 2021)
Substance addiction is a knotty worldwide public health problem. It endangers both personal life and social stability, causing great loss on economy. Substance-related disorder is considered to be a complicated chronic brain disorder. It’s resulted from interactions among pharmacological properties of addictive substance, individual susceptibility and social-environmental factors. Unfortunately, there is still no ideal treatment for this disorder. Recent evidences suggest that gut microbiota may play an important role in the pathogenesis of neuropsychiatric disorders, including substance-related disorders. This review summarizes the research on the relationship between gut microbiota and substance related disorders, including different types of substance, different individual susceptibility, the occurrence and development of substance-induced mental disorders. We also discuss the potentiation of gut microbiota in the treatment of substance related disorders, especially in the treatment of substance-induced mental disorders and manipulation on individuals’ responsiveness to addictive substances.